Regional, national and international networks: the suitability of different competitive strategies for different geographic profiles - Cesário, M. (2014)
The aim of this paper is to conduct an exploratory investigation on the type of competitive strategies that are likely to be associated with different networking profiles. We focus our attention on response strategies related to investments and technological adjustments, and how they vary according to different spatial scales of firms' networks. We report the results of the application of a common questionnaire to a sample of 165 SMEs from labour-intensive sectors belonging to southern Europe. Using cluster analysis, the firms were grouped according to the use of regional, national and international geographic scales for supply, distribution and sales networks. For each group, response strategies were analysed. Our results allow us to observe that there is a relation between the capacity to improve the geographic scale of networking and the capacity to strategically react to changing market conditions.